2020
DOI: 10.15372/rgg2019146
|View full text |Cite
|
Sign up to set email alerts
|

Phase Relations of Iron Carbides Fe2C, Fe3C, and Fe7C3 at the Earth’s Core Pressures and Temperatures

Abstract: —Based on first-principle calculations in the framework of the density functional theory and structure prediction algorithms, we have determined iron carbide phases stable at the Earth’s core pressures and temperatures. It is shown that Fe7C3 is unstable and decomposes into the mixture Fe2C + Fe3C over the entire range of pressures and temperatures specific to the Earth’s inner core. Subsequent decomposition of Fe3C into the mixture Fe + Fe2C is unfavorable. We also predict a new low-temperature modification F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…All structures are dynamically stable, which was confirmed using the calculated phonon spectra (Figure ). Fe 3 N- C 2/ m is isostructural to Fe 3 C- C 2/ m -II . In this structure, nitrogen atoms are bonded to 7 Fe atoms, forming [FeN 7 ] one-capped trigonal prisms connected with each other by edges and faces (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…All structures are dynamically stable, which was confirmed using the calculated phonon spectra (Figure ). Fe 3 N- C 2/ m is isostructural to Fe 3 C- C 2/ m -II . In this structure, nitrogen atoms are bonded to 7 Fe atoms, forming [FeN 7 ] one-capped trigonal prisms connected with each other by edges and faces (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, a recent theoretical study has predicted a new monoclinic high‐ P phase for Fe 7 N 3 and Fe 7 C 3 above ∼250 GPa (Sagatov et al., 2019). Subsequent simulations suggested that Fe 7 C 3 might decompose into the mixture of Fe 2 C and Fe 3 C at conditions of the Earth's inner core (Sagatov et al., 2020). Whether these results could be applied in the Fe‐N‐C ternary system is still under debate.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the cutoff energy was increased to 1000 eV. The calculation of the Gibbs free energy dependence on temperature was performed according to the methodology described in our previous work. , …”
Section: Methodsmentioning
confidence: 99%